Upregulation of interleukin‐1β/transforming growth factor‐β1 and hypoxia relate to molecular mechanisms underlying immobilization‐induced muscle contracture. Issue 3 (30th June 2015) - Honda, Yuichiro; Sakamoto, Junya; Nakano, Jiro; Kataoka, Hideki; Sasabe, Ryo; Goto, Kyo; Tanaka, Miho; Origuchi, Tomoki; Yoshimura, Toshiro; Okita, Minoru
ABSTRACT Introduction: In this study we investigated the molecular mechanism underlying muscle contracture in rats. Methods: The rats were divided into immobilization and control groups, and soleus muscles of the right and left sides were selected for analyses. Results: The levels of CD11b and α‐SMA protein, IL‐1β, and TGF‐β1 mRNA, and type I and III collagen protein and mRNA were significantly greater in the immobilization group than in the control group at all time‐points. HIF‐1α mRNA levels were significantly higher in the immobilization group at 4 weeks. Moreover, HIF‐1α, α‐SMA, and type I collagen levels were significantly higher at 4 weeks than at 1 and 2 weeks in the immobilization group. Conclusions: In the early stages of immobilization, upregulation of IL‐1β/TGF‐β1 via macrophages may promote fibroblast differentiation that could affect muscle contracture. The soleus muscle became hypoxic in the later stages of immobilization, suggesting that hypoxia influences the progression of muscle contracture. Muscle Nerve 52:419–427, 2015